Atopic Dermatitis and Psoriasis as Overlapping Syndromes. (28th November 2020) - Bozek, A.; Zajac, M.; Krupka, M.
Abstract : Background/Objectives . Cooccurrence of atopic dermatitis (AD) and psoriasis (PS) is not common. However, both diseases are still of interest because of their comprehensive and diverse mechanisms. This study aimed to present the clinical and immunological profiles of patients with concomitant AD and PS and compare them with those of patients with only one of the diseases. Methods . In this observational study, 38 children with concomitant AD and PS with a mean age of 6.5 ± 3.2  yrs were compared with 41 similar patients with AD only (5.3 ± 5.1  yrs) and 28 patients with PS only (6.4 ± 4.3  yrs). All patients underwent dermatological examinations, including determination of SCORAD and PASI scores. TNF- α, IFN- γ, IL-2, IL-4, IL-5, IL-6, IL-8, IL-12, IL-17, IL-18, IL-22, I:-33, and TARC/CCL17 were measured by ELISA according to the manufacturer's instructions. Results . Patients with concomitant AD and PS were frequently boys and overweight and had skin lesions equally distributed throughout the body. Children with concomitant AD and PS were more likely to report a family history of atopic disease than children with only AD or PS, and those with AD were more likely to report a family history of atopic disease than those with PS. Significant differences were observed in the concentration of IL-17 between patients with AD and PS and those with only AD or PS: 9.1 ± 3.7  pg/ml vs. 4.8 ± 2.9  pg/ml; and 9.1 ± 3.7  pg/ml vs. 5.2 ± 3.9  pg/ml, respectively (PD vs. AD, p = 0.01 ; PD vs. PS, p = 0.03 ). Conclusions . AD and PS can coexist. The role of T helper 17 cells may be more essential than believed.